Restructuring of the Diabetes Day Centre: a pilot lean project in a tertiary referral centre in the West of Ireland. Issue 8 (30th May 2013) - McDermott, A M; Kidd, P; Gately, M; Casey, R; Burke, H; O'Donnell, P; Kirrane, F; Dinneen, S F; O'Brien, T
Abstract : Introduction: Diabetes is a chronic disease amenable to management in the community and outpatient setting. The increasing incidence of diabetes places outpatient endocrinology services under pressure to provide a quality service in a timely manner. Our aim was to apply lean thinking to the diabetes clinic in a tertiary referral centre in the West of Ireland to improve flow, as reflected in reduced patient journey times. Methods: The project lasted 6 months, from January to June 2011. An introductory seminar on lean thinking was arranged to inform and motivate the Diabetes Day Centre staff. Two 'rapid improvement events' took place. Value stream mapping (VSM) was the predominant lean tool employed. Patient journeys were mapped and quantified (minutes) using timesheets allocated to each step in the process at baseline, and following intervention. Data were analysed using Minitab V.16.0. Results: VSM allowed the value-adding and problem-causing steps in the patient journey through the diabetes clinic process to be identified and addressed. Total patient journey time through the clinic was significantly reduced from 118 (±38.02) min to 58 (±18.30) min (p<0.001). Conclusions: This project reflects the successful application of VSM as a lean tool in a pilot study at our institution as evidenced by improved patient flow and a significant reduction in patient journey time through the clinic. Through the incorporation of Lean into the ethos of the hospital, we have the potential to deliver excellent care in a safe environment and in an efficient manner, while benefiting the patient, employees and tax-payer.